2022
DOI: 10.1021/acs.jpcc.2c05385
|View full text |Cite
|
Sign up to set email alerts
|

Role of Coatings as Artificial Solid Electrolyte Interphases on Lithium Metal Self-Discharge

Abstract: Artificial solid electrolyte interphases have provided a path to improved cycle life for high energy density, next-generation anodes like lithium metal. Although long cycle life is necessary for widespread implementation, understanding and mitigating the effects of aging and self-discharge are also required. Here, we investigate several coating materials and their role in calendar life aging of lithium. We find that the oxide coatings are electronically passivating whereas the LiF coating slows charge transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…We here hypothesize that strategically applied pressure may also improve calendar aging by reducing the propensity for dead Li formation during cycling. Our previous work has shown that calendar aging is dominated by stranded Li that is reconnected by cycling between rest steps (Merrill et al, 2021;Merrill et al, 2022) and, separately, that increasing applied interfacial pressure results in denser Li films with larger grains during cycling (Harrison et al, 2017;Harrison et al, 2021a;Harrison et al, 2021b). Therefore, the novel combination of applied pressure and cycling between rest steps should prevent or reconnect Li that becomes stranded during calendar aging.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We here hypothesize that strategically applied pressure may also improve calendar aging by reducing the propensity for dead Li formation during cycling. Our previous work has shown that calendar aging is dominated by stranded Li that is reconnected by cycling between rest steps (Merrill et al, 2021;Merrill et al, 2022) and, separately, that increasing applied interfacial pressure results in denser Li films with larger grains during cycling (Harrison et al, 2017;Harrison et al, 2021a;Harrison et al, 2021b). Therefore, the novel combination of applied pressure and cycling between rest steps should prevent or reconnect Li that becomes stranded during calendar aging.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggests that galvanic corrosion is correlated with the amount of Li coverage on the current collector and is, therefore, capacity (or cell geometry)dependent (Lin et al, 2019;Leung et al, 2022). Dead Li can form during calendar aging as another potential capacity loss mechanism, but there is some debate over how much capacity loss during rest is related to corrosion versus dead Li (Boyle et al, 2021;Merrill et al, 2021;Merrill et al, 2022). This likely depends on many factors, including the electrolyte, counter-electrode, and electrochemical conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrodeposited Li is particularly susceptible to aging as it is highly porous, is composed of many small grains, and suffers from the tendency to form dendritic and other high surface area mossy structures. While bulk Li metal has been investigated within the scope of integrating protection layers or artificial SEIs, these studies are typically restricted to relatively short timeframes of hours to weeks (Yang et al, 2008;Kozen et al, 2017;Lin et al, 2019;Gao et al, 2020;Kolesnikov et al, 2020;Boyle et al, 2021;Merrill et al, 2021;Merrill et al, 2022). Predictive models and computational studies have been used to supplement these studies and can be used to determine limitations over longer term aging (Wood et al, 2018;Dessantis et al, 2023).…”
Section: Introductionmentioning
confidence: 99%